Penerapan Metode SCRUM dalam Pengembangan Sistem Informasi Layanan Kawasan - Warkim Warkim; Muhamad Hanif Muslim; Farham Harvianto; Setiawan Utama (Maranatha University Press, 2020)
The development of technology is very influential in the business processes of an organization to be able to carry out its duties and functions. As a government agency engaged in research, the Indonesian Institute of Sciences (LIPI) needs to make organizational changes to support its vision as a world-class research institution. One of the first steps taken is reorganizing and redistributing employees that have a high impact on the business process of service to employees because the supporting resources are placed corporately and no longer in the work units. To deal with this problem, we developed a Regional Service Information System using the Scrum methodology. The output is a web-based software that facilitates service requests needed by employees, ranging from service submission, processing by the Area Manager and Central Manager, to being received again by the service requester. The Regional Service Information System is expected to be a solution to the problems that arise as a result of the redistribution of employees at LIPI and to improve the effectiveness of employees as the research supporting resources.